Distribution, transmission and disease characterization of sweetpotato feathery mottle virus - Palomar, Manuel K.; Barsalote, E.B.; Colis, H.S.V. (Annals of Tropical Research, 2000)
Sweetpotato feathery mottle virus (SPFMV) disease was observed in the sweetpotato fields of the Visayas State College of Agriculture and adjacent barangays with infection ranging from 2.8 to 21.0%. Likewise, in the the germplasm collection of the Philippine Root Crop Research and Training Center, 21.0% of the 1,124 sweetpotato accessions were infected with SPFMV, 8.0% of which were severely infected. Transmission studies showed that SPFMV was mechanically and biologically transmissible but not seedbome. SPFMV was mechanically transmitted to true seedlings (2-5 leaf stage) but not to vegetative cuttings and tuber sprouts. It was also non-persistently transmitted by the melon aphid (Aphis gossypii Glover). The acquisition feeding and inoculation feeding periods of the aphid were 56 sec and 15-60 sec, respectively. Serial transmission trials revealed that the insect could transmit the disease up to 5 plants after a single acquisition feeding only. There were two stains of SPFMV based on disease symptoms in sweetpotato and in reaction to certain host plants. Both strains showed similar transmissibility and physical properties in vitro.